Generation of Adenovirus Vectors Devoid of All Viral Genes by Recombination between Inverted Repeats - Steinwaerder, Dirk S. (American Society for Microbiology, 1999)
Direct or inverse repeated sequences are important functional features of prokaryotic and eukaryotic genomes. Considering the unique mechanism, involving single-stranded genomic intermediates, by which adenovirus (Ad) replicates its genome, we investigated whether repetitive homologous sequences inserted into E1-deleted adenoviral vectors would affect replication of viral DNA. In these studies we found that inverted repeats (IRs) inserted into the E1 region could mediate predictable genomic rearrangements, resulting in vector genomes devoid of all viral genes. These genomes (termed ΔAd.IR) contained only the transgene cassette flanked on both sides by precisely duplicated IRs, Ad packaging signals, and Ad inverted terminal repeat sequences. Generation of ΔAd.IR genomes could also be achieved by coinfecting two viruses, each providing one inverse homology element. The formation of ΔAd.IR genomes required Ad DNA replication and appeared to involve recombination between the homologous inverted sequences. The formation of ΔAd.IR genomes did not depend on the sequence within or adjacent to the inverted repeat elements. The small ΔAd.IR vector genomes were efficiently packaged into functional Ad particles. All functions for ΔAd.IR replication and packaging were provided by the full-length genome amplified in the same cell. ΔAd.IR vectors were produced at a yield of ∼10(4) particles per cell, which could be separated from virions with full-length genomes based on their lighter buoyant density. ΔAd.IR vectors infected cultured cells with the same efficiency as first-generation vectors; however, transgene expression was only transient due to the instability of deleted genomes within transduced cells. The finding that IRs present within Ad vector genomes can mediate precise genetic rearrangements has important implications for the development of new vectors for gene therapy approaches.